Laryngeal aging and acoustic changes in male rat ultrasonic vocalizations. Issue 8 (20th July 2012) - Peterson, Jennifer R.; Watts, Christopher R.; Morris, Jesse A.; Shelton, John M.; Cooper, Brenton G.
Abstract This study examined changes in the acoustic and temporal structure of ultrasonic vocalizations as a function of age and correlated acoustic changes with vocal fold microstructure. Ultrasonic vocalizations were recorded in three age groups of male rats: aged (24–26 months), middle‐aged (17–18 months), and young (4–5 months). Acoustic and structural changes in vocal fold tissue were evident by 18 months of age. Histological analyses revealed decreased density of elastin and hyaluronic acid and increased collagen density in the middle‐aged and aged groups compared to the young rats. Laryngeal microstructure correlated with some of the ultrasonic acoustic features. These results show that male Long Evans rats experience changes in ultrasonic acoustic structure by middle age, and these changes correlate with deterioration in laryngeal microstructure. Ultrasonic vocalizations can be used as a model system for age‐related degeneration in vocal fold structure and function. © 2012 Wiley Periodicals, Inc. Dev Psychobiol 55: 818–828, 2013.